Research progress on DNA hydroxymethylation in atrial fibrillation: a review - Fan, Shaowei; Shi, Jingjing (Frontiers in Pharmacology, 2025)
Epigenetic modifications play a critical role in the pathogenesis and progression of cardiovascular diseases. Among these, DNA hydroxymethylation has garnered increasing attention in the fields of oncology, hematology, and neurological disorders, serving as a key mechanism for untangling molecular pathways underlying disease etiology. Although emerging evidence has begun to illuminate the role of DNA hydroxymethylation in cardiovascular conditions such as coronary artery disease and atherosclerosis, its implications in atrial fibrillation remain underexplored. This review aims to summarize current understanding and discuss potential mechanisms through which DNA hydroxymethylation may contribute to the development and progression of atrial fibrillation.